Pengaruh Strategi Pembelajaran Rotating Trio Exchange pada Materi Ekosistem terhadap Aktivitas dan Hasil Belajar Siswa Kelas X di Madrasah Aliyah Kedaisianam - Lailatul Husna (Symbiotic: Journal of Biological Education and Science, 2021)
This study aims to determine the effect of the Rotating Trio Exchange learning strategy on ecosystem materials on the activities and learning outcomes of class X students at Madrasah Aliyah Kedaisianam. The research design used for this research is in the form of the Nonequevalent Control Group Design. Data collection techniques using pretest-posttest and observation sheets. In this study, it is know that there is an effect of the Rotating Trio Exchange learning strategy on activities as evidenced by the average by the average value of the percentage of student learning activities in the good category.While in the control class the average percentage value of student learning activities is in the sufficient category. The learning outcomes obtained were 55.95 (pretest) and 90.00 (posttest) for the experimental class and the average learning outcomes in the control class were 53.33 (pretest) and 84.76 (posttest). For the results of the t-test, it is found that tcount 3.20 while ttable 2.09. This means that Ho is rejected and Ha is accepted. Therefore, it can be proven that the Rotating Trio Exchange strategy has an effect on the activities and learning outcomes of class X students at Madrasah Aliyah.